1977
DOI: 10.1346/ccmn.1977.0250102
|View full text |Cite
|
Sign up to set email alerts
|

Adsorbed Molecules on Solvated Layer Silicates: Surface Mobility and Orientation from ESR Studies

Abstract: Abstract--The adsorption of nitroxide spin probes on smectites solvated in liquids of greatly different polarity was studied using electron spin resonance (ESR) spectroscopy. Adsorbed probes demonstrate various degrees of restricted rotational motion and alignment at the silicate surfaces, depending upon the properties of the solvating liquid. The results are interpreted in terms of direct surface-molecule interaction modified by solvent competition effects. A fraction of the probe molecules is immobilized in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…There is evidence in other porous systems that molecules preferentially align along surfaces when adsorbed . Adsorption of fluids on clays also shows ordering with nonrandom tumbling of molecules close to the clay surface . If a system were to have no preferential orientation of the fluid molecules at pore surfaces, then the dipolar coupling will simply be an average over all angles and no anisotropy in the relaxation will occur.…”
Section: Homonuclear Dipolar Couplingmentioning
confidence: 99%
“…There is evidence in other porous systems that molecules preferentially align along surfaces when adsorbed . Adsorption of fluids on clays also shows ordering with nonrandom tumbling of molecules close to the clay surface . If a system were to have no preferential orientation of the fluid molecules at pore surfaces, then the dipolar coupling will simply be an average over all angles and no anisotropy in the relaxation will occur.…”
Section: Homonuclear Dipolar Couplingmentioning
confidence: 99%
“…Evidence for the mechanisms by which metals are retained in exchangeable (or nonexchangeable) form may also be derived from the degree of surface mobility. Recent investigations of organic cation rotation at clay surfaces by electron spin resonance (ESR) spectroscopy (McBride, 1976a;McBride, 1977) have demonstrated that motion-dependent ESR spectra of adsorbed paramagnetic cations can provide useful information about adsorption processes. Spectra of the vanadyl ion, VO ~+, are particularly well suited to estimation of rates of rotational motion because of the strong dependence of spectral lineshape upon rotational correlation time, rR, where rR represents the time required for VO ~+ to reorient in solution by random thermal tumbling.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive ESR work has been undertaken on the dynamical behaviour ofnitroxide spin probes such as TEMPO +, the cationic form of 4-amino-2,2,6,6-tetramethylpiperdine-Noxide, in the interlamellar region of smectites. (McBride 1976c(McBride , 1976d(McBride , 1977a(McBride , 1977b. Rotational correlation times were derived from the theory of Sachs & Latorre (1974).…”
Section: Nitroxide Spin Probesmentioning
confidence: 99%
“…4 illustrates the ESR spectra of orientated films of TEMPO +-doped Na +-hectorite solvated with water, methanol and ethanol. For the fully hydrated Na+-hectorite, McBride (1977b) related the calculated value of zc to an effective diffusion coefficient of D = 5 • 10 -6 cmZs -l using the relationship D = 12/4Zc, where/is the mean jump distance, i.e. the diameter of the probe molecule.…”
Section: Nitroxide Spin Probesmentioning
confidence: 99%